PHÂN TÍCH CÁC YẾU TỐ ĐỊA MẠO PHỤC VỤ ĐÁNH GIÁ TIỀM NĂNG VÀ KHAI THÁC NHANH VÀNG SA KHOÁNG KHU VỰC THƯỢNG NGUỒN SÔNG SEKAMAN - CHDCND LÀO - Hà, Phạm Việt; Liêm, Ngô Văn; Hoàn, Bùi Thị Lê (Vietnam Journal of Earth Sciences, 2012)
Analysis of geomorphological factors for potential assessment and quick exploitation of gold placer deposits in the upstream area of Sekaman River, Lao’s PDR The upstream area of Sekaman River at San Xay district, Atapu provine, Lao’s PDR will be the water reservoir of hydroelectric plants in the near future. Thus, the intensive rapid exploitation of precious mineral ores in this region plays an important role in the national economy. In this paper, we present one of the applied geomorphological researches in the exploration of minerals, particularly gold placers in the upstream area of Sekaman River. Results showed that most of the positions which are terrace and alluvial terrain with higher capacity of accumulating minerals and placer gold. The initial result is adequate to meet the requirements as a basis for orientation in field sampling assessment of reserves of placer gold mining at Sekaman River area.